Laparoscopic Sleeve Gastrectomy as a Primary Operation for Morbid Obesity: Experience with 200 Patients. (3rd June 2012) - Gentileschi, Paolo
Abstract : Introduction . Laparoscopic sleeve gastrectomy (LSG) represents a valid option for morbid obesity, either as a primary or as a staged procedure. The aim of this paper is to report the experience of a single surgeon with LSG as a standalone operation for morbid obesity. Methods . From April 2006 to April 2011, 200 patients underwent LSG for morbid obesity. Each patient record was registered and prospectively collected. In July 2011, a retrospective analysis was conducted. Results . Patients were 128 females and 72 males with a median age of 40.0 years. Median pre-operative BMI was 49.4 kg/m 2 . Median follow-up was 27.2 months. Median post-operative BMI was 30.4 kg/m 2 . Median %excess weight loss (%EWL) was 63.6%. Median post-operative hospital stay was 4.0 days in the first 84 cases and 3.0 days in the last 116 cases. Six major post-operative complications occurred (3%): two gastric stump leaks (1%), three major bleedings (1.5%) and 1 (0.5%) bowel obstruction. One case of mortality was registered (0.5%). To date only 4 patients are still in the range of morbid obesity (BMI > 35 kg/m 2 ). Conclusions . Laparoscopic sleeve gastrectomy is a formidable operation in the short-term period. Median %EWL in this series was 63.6% at 27.2 months follow-up.